2019
DOI: 10.1111/apha.13377
|View full text |Cite
|
Sign up to set email alerts
|

LTBP2 knockdown by siRNA reverses myocardial oxidative stress injury, fibrosis and remodelling during dilated cardiomyopathy

Abstract: Aim Dilated cardiomyopathy (DCM) is characterised by left ventricular dilation and associated with systolic dysfunction. Recent evidence has reported the high expression of latent transforming growth factor beta binding protein 2 (LTBP2) in heart diseases, which may play a role in regulating multiple biological functions of myocardial cells. Thus, this study set out to investigate the molecular mechanism and effects of LTBP2 in myocardial oxidative stress injury, fibrosis and remodelling in a rat model of DCM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
(84 reference statements)
3
21
0
Order By: Relevance
“…The DOX mouse model also exhibits progressive cardiac functional decline and ventricular dilation (29), which is consistent with the diagnosis of dcM. In addition, while the specific pathogenesis of DCM and the mechanism of its progressive progression remain unknown, previous studies revealed that the development of dcM may be associated with decreased mitochondrial function (56), abnormal oxidative stress (57,58), as well as excessive myocardial apoptosis and necrosis (59,60). In line with these possible causes, it has also been reported that the DOX model is accompanied by similar mitochondrial dysfunction (29,61), oxidative stress injury (62) and apoptotic changes (63).…”
Section: Discussionsupporting
confidence: 64%
“…The DOX mouse model also exhibits progressive cardiac functional decline and ventricular dilation (29), which is consistent with the diagnosis of dcM. In addition, while the specific pathogenesis of DCM and the mechanism of its progressive progression remain unknown, previous studies revealed that the development of dcM may be associated with decreased mitochondrial function (56), abnormal oxidative stress (57,58), as well as excessive myocardial apoptosis and necrosis (59,60). In line with these possible causes, it has also been reported that the DOX model is accompanied by similar mitochondrial dysfunction (29,61), oxidative stress injury (62) and apoptotic changes (63).…”
Section: Discussionsupporting
confidence: 64%
“…We noted three genes, Postn (periostin), Ltbp2 (latent TGF-β binding protein 2), and Thbs4 of interest in cluster 5. While Postn, an ECM protein, is critical for tissue development and regeneration and plays a role in wound healing and ventricular remodeling in myocardial events 41 , Ltbp2 and Thbs4 have roles in myocardial fibrosis in DCM 42 or the fibrotic process 43 . Similarly, three transcripts, Apoe , Tgfbi, and Mfap4, were found interesting in cluster 6.…”
Section: Resultsmentioning
confidence: 99%
“…Our scRNAseq analysis revealed 12 distinct clusters that express overlapping genes ( Fig 4A, B, C ). Several of these ( Wif1a, Npy ) 47 have been previously shown to be involved in wound healing, ventricular/cardiac remodeling, and myocardial fibrosis in DCM pathogenesis ( Ltbp2 , Thbs4 and Tgfbi ) 24, 42, 43 . However, a subset of genes ( Mt1, Mt2, Cxcl1 ) 25, 30 that have immune modulatory roles and promote angiogenesis ( Vegfd ) were also detected in various clusters.…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study investigated the role of LTBP2 in these processes. 11 Lamin A/C ( LMNA ) mutation causes not only DCM but also heart block. The mechanism underlying LMNA nonsense mutation-induced cardiac conduction defects through atrioventricular (AV) node fibrosis is upregulated extracellular cellular matrix gene expression upon activation of cardiac apoptosis; this explains heart block in LMNA mutation-carrying DCM patients.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%